Intercultura, formação de professores e cotas nas universidades brasileiras: Uma realidade efetiva ou formal? - Friedrich, Rafael (2019)
The construction of the history of Brazil after the years of 1.500 d.C., beginning of Portuguese colonization, evidence a social organization strongly marked by the relations of power hierarchy, initially with the regime of black and Indian slavery, posteriorly, for social inequality propagated over the years. As a consequence, some groups were historically privileged with better conditions of study and better job opportunities, making it necessary to adopt public policies able to reduce the effects of these inequalities, admittedly existing, among the various groups in society that make up the large Brazilian population. Affirmative Actions, through the Quota System, arise in this yearning and aim at the realization of equal opportunities and the neutralization of the effects of discrimination, having been implemented in a disparate manner by the Brazilian universities as a criterion in the selection of students since 2003. As a result, the following Research Questionnaire: How is the inclusion of the quota student in the Brazilian Universities happening? As a way to answer this question, we outlined the following General Objective: To contribute with theoretical and epistemological subsidies, in an intercultural perspective of study, for the formation of teachers, in order to effectively include students in university the Quota System, which has been divided into the following Specific Objectives: Map if there was adhesion to the Quota System by the Brazilian Higher Education Institutions (1); To investigate the actions taken by five Brazilian Universities to effectively include students in the Quota Policy (2); Organize the collected data and identify which measures have been adopted positively for the effective inclusion of quota holders (3); To contribute to the formation of teachers with the proposition of theoretical-epistemological subsidies that help in the effective inclusion (not just formal) of quotative students as subjects who learn and transmit knowledge, from the perception of difference as something promising (4). For that, I not only adopted qualitative research as methodology, but also, as a process of execution, where method is trajectory to reach the proposed Objectives, with the direct concern of the researcher with the experience as lived, felt or experienced. The writing of this thesis with the thematic of the Interculture, because I understand it is vital that intercultural subsidies be produced to effectively include the students entrance in the Universities by the Quota System, respecting, accepting and legitimizing their differences. I continue writing to address the theme of Human Rights and the Equality Principle, aiming to provide some understanding to the reader about the origin and formation of individual and collective rights, so absent at this moment that Brazil is going through. Still, among other topics, including the historical construction of Affirmative Policies in Brazil, I sought to map the formal adherence of the Quota System by Higher Education Institutions (IES), I intend to verify if policies and measures are being adopted to make this inclusion process effective. Finally, having in hand the whole theoretical framework that constituted the research, I close the writing analyzing the data collected and proposing a response to the question investigated.